(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Menstrual hygiene is defined as the principle of maintaining and keeping our body clean during menstrual flow. The basic requirement for keeping ourselves clean requires appropriate sanitary pads, clothes, soakage materials, water, soap and toilet facilities with privacy. Menstrual hygiene management is one of the most important aspect of hygiene for women and adolescent girls in their life. In today’s world the need of the hour is to give utmost importance to the health and hygiene of an individual. But the fact is despite being an important aspect which concerns women and girls in menstruating group. We often see that it has not been addressed as much as it should be. Menstrual hygiene is often neglected and not much has been talked about. The time has come to raise awareness and make enough campaign in the remote and far flung areas, so that the health and hygiene improves. The paper will bring forth the study as to why menstrual hygiene is important and what steps one should take to lead a healthy life.